1995
DOI: 10.1073/pnas.92.17.7690
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutathione in the export of compounds from cells by the multidrug-resistance-associated protein.

Abstract: Multidrug-resistance-associated protein [6][7][8] and is able to decrease cellular drug levels against a concentration gradient (4, 6). However, recent work has also indicated interesting differences between MRP and Pgp. Increased cellular MRP levels are associated with increased reduced glutathione (GSH) S-conjugate carrier (GS-X pump) activity in isolated plasma membrane vesicles (9-11). This suggests that MRP is a GS-X pump (12) present in many, if not all, mammalian cells (9-13). These pumps transport sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
298
2
7

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 436 publications
(318 citation statements)
references
References 35 publications
11
298
2
7
Order By: Relevance
“…The evidence available suggests that such conjugates do not exist for anthracyclines or vinca alkaloids (Tew, 1994). Zaman et al (1995) analysed the medium from MRP1-overexpressing cells incubated in the presence of vincristine or daunorubicin and found that all drug recovered was in the unmodified form. The simplest interpretation of our data is that vinblastine is transported as free drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence available suggests that such conjugates do not exist for anthracyclines or vinca alkaloids (Tew, 1994). Zaman et al (1995) analysed the medium from MRP1-overexpressing cells incubated in the presence of vincristine or daunorubicin and found that all drug recovered was in the unmodified form. The simplest interpretation of our data is that vinblastine is transported as free drug.…”
Section: Discussionmentioning
confidence: 99%
“…Besides organic anions MRP1 can also transport neutral and basic cytotoxic drugs not known to be conjugated to GSH or other negatively charged compounds Zaman et al, 1994). Nevertheless, MRP1 requires the presence of intracellular glutathione for the transport of these drugs (Versantvoort et al, 1995;Zaman et al, 1995). The data available are most consistent with a model in which MRP1 co-transports cytotoxic drugs with GSH (Rappa et al, 1997;Loe et al, 1998).…”
mentioning
confidence: 90%
“…SI(MRP) is a subline of the human non-small cell lung cancer cell line SW-1573/S1 that overexpresses MRP 15-fold [3,8]. This cell line was obtained by transfection of S1 ceils with an expression vector containing MRP cDNA and a neomycin-resistance gene and selection with Geneticin (G418) [3].…”
Section: Cell Lines and Yeast Strainsmentioning
confidence: 99%
“…(ii) MRP requires GSH to export anti-cancer drugs and arsenite out of the cell [8]. (iii) Drug transport by MRP is relatively insensitive to classic reversal agents of Pgp-mediated multidrug resistance (MDR), such as verapamil and cyclosporin (analogues) [2,3], but is modulated by inhibitors of organic anion transport, such as probenecid and sulfinpyrazone [6,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation